2008
DOI: 10.1111/j.1532-950x.2008.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Complications After Large Colon Resection and End‐to‐End Anastomosis for Strangulating Large Colon Volvulus in Seventy‐Three Horses

Abstract: Horses that survive the early postoperative period and are discharged after large colon resection and anastomosis have a good chance for long-term survival with minimal negative impact on quality of life and use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 13 publications
2
62
0
Order By: Relevance
“…Ellis et al . reported that 74% (54/73) of horses with large colonic volvulus treated with colonic resection survived to hospital discharge, with a mean duration of 4 h of colic signs prior to admission . In another study, 47% (16/34) of horses with a strangulating large colon volvulus treated with colonic resection survived to discharge, with a median duration of 7 h colic prior to admission .…”
Section: Discussionmentioning
confidence: 98%
“…Ellis et al . reported that 74% (54/73) of horses with large colonic volvulus treated with colonic resection survived to hospital discharge, with a mean duration of 4 h of colic signs prior to admission . In another study, 47% (16/34) of horses with a strangulating large colon volvulus treated with colonic resection survived to discharge, with a median duration of 7 h colic prior to admission .…”
Section: Discussionmentioning
confidence: 98%
“…The narrow areas are prone to obstruction by digesta or foreign materials [1,2] . Large colon volvulus is a common cause of surgical colic in horses and has a high mortality [3] . Even resection does not remove all ischemic colon and recovery of the remaining mucosa can determine the severity of post-operative endotoxaemia and outcome [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Large colon volvulus is a common cause of surgical colic in horses and has a high mortality [3] . Even resection does not remove all ischemic colon and recovery of the remaining mucosa can determine the severity of post-operative endotoxaemia and outcome [3] . Because most horses with gastrointestinal diseases are routinely treated with non-steroidal antiinflammatory drugs (NSAIDs), such as flunixin meglumine and these drugs can be toxic to normal equine gastrointestinal mucosa [4] , the effects of NSAIDs on repair of equine intestinal mucosa are important [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The concern with such cases relates to the ability of affected intestine to heal and regain function without causing severe postoperative complications and death. Large colon volvulus can be diagnosed in up to 26% of horses that require emergency abdominal surgery (Fisher andMeagher 1985, Mair andSmith 2005), and is a rapidly progressive, life-threatening form of colic with fatality rates between 30 to 80% , Mair and Smith 2005, Ellis et al 2008. Although documented in horses of any age, breed and gender, broodmares are more likely to develop large colon volvulus 1 to 3 months after foaling , Embertson et al 1996.…”
Section: Intestinal Ischemia In Horses -Clinical Diseasementioning
confidence: 99%
“…In horses with large colon volvulus, some ischemic intestine can be inaccessible for resection so that ischemic tissue is left in place and must even support anastomotic healing (Driscoll et al 2008, Ellis et al 2008. If the colon is considered viable or resection is not justified because of expense or a perceived perception of low risk for recurrence, then the entire organ is left in place to recover from the ischemic insult.…”
Section: Intestinal Ischemia In Horses -Clinical Diseasementioning
confidence: 99%